Use of the IPAQ questionnaire in the form of a mobile application in monitoring physical activity of patients with cardiovascular diseases - Tomasz Saran (Annals of Agricultural and Environmental Medicine, 2018)
Introduction Systematic, dynamic physical effort brings about tremendous health benefits, not only in young individuals, but as a form of primary prevention, and primarily as secondary prevention of cardiovascular system diseases.